GREEN BANKING DAN RASIO KECUKUPAN MODAL MEMPENGARUHI PERTUMBUHAN LABA BANK UMUM SYARIAH DI INDONESIA - Gustika Nurmalia (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The research objective is to determine the effect of green banking and the capital adequacy ratio on the profit growth of Islamic commercial banks in Indonesia in 2016 – 2019 and analyze Islamic views regarding Green Banking. This study is a quantitative study using secondary data in the form of a published annual report and samples taken from the financial statements of 9 Islamic commercial banks for the 2016-2019 period. The researcher uses the green coin rating indicator in measuring green banking and CAR as an independent variable and then profit growth as the dependent variable. The data analysis technique used is panel data regression with Eviews 11 software. The results of the research that the partial test shows that there is no effect between green banking and CAR and profit growth. This happens because banks have only begun to optimally implement green banking in 2019. And banks are too stable to maintain CAR above 8% and even increase every year, but profit growth decreases every year and there are even negative numbers. Meanwhile, the independent variables simultaneously affect the dependent variable. Islam teaches not to do damage and optimize capital so that the green banking concept is in line with sharia principles.